An ultrasensitive electrochemiluminescent sensor based on a pencil graphite electrode modified with CdS nanorods for detection of chlorogenic acid in honeysuckle. (20th December 2016) - Zheng, Ruijuan; Zhong, Jianhai; Zhao, Chenhao; Lang, Xiaoling; Hu, Zhibiao; Luo, Jiangshui
Abstract: In this paper, a novel and ultrasensitive electrochemiluminescent sensor employing a solvothermal‐synthesized CdS nanorod‐modified pencil graphite electrode (CdS/PGE) for the determination of chlorogenic acid (CA) is fabricated. In the first step, the PGE surface is modified using CdS nanorods. In the next step, the developed electrode is used to detect CA using a electrochemiluminescent (ECL) technique, in which potassium persulfate (K2 S2 O8 ) served as a co‐reactant. The possible ECL mechanism is investigated, and the influences of pH and cyclic voltammetric scanning rate on the signal response are studied. The ECL intensity decreases quantitatively in relation to the concentration of the target molecule. Under optimized conditions, the linear correlation between the quenched ECL intensity and the logarithm of CA concentration is observed in the range from 2 × 10 −9 to 8 × 10 −7 mol L −1 with a limit of detection of 1 × 10 −9 mol L −1 . This proposed method is applied to the analysis of CA in honeysuckle flower, giving recoveries of 99‐107%. The experimental results demonstrate that this ECL sensor shows good stability and reproducibility.